2018
DOI: 10.1186/s12875-018-0864-9
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and cessation of mental healthcare after mental health screening in primary care: a prospective cohort study

Abstract: BackgroundMental health (MH) problems have considerable personal and societal implications. Systematic MH screening may raise general practitioners’ (GP) awareness of the current need of treatment in their listed patients. The focus of MH screening has so far been on increasing diagnostic rates and treatment of mental disorders, whereas cessation of MH treatment after normal test results has rarely been studied. This study aims to examine the mental healthcare trajectories after MH screening combined with feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Therefore, we believe that our results only reveal the tip of the iceberg; the most vulnerable populations were probably not reached by our study. Health authorities should take adequate measures to train health professionals on screening and identifying these disorders in both general and primary healthcare settings, and refer them for specialized medical management ( Geyti et al, 2018 ). Moreover, improving access to psychiatric care is also recommended, taking the example of developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we believe that our results only reveal the tip of the iceberg; the most vulnerable populations were probably not reached by our study. Health authorities should take adequate measures to train health professionals on screening and identifying these disorders in both general and primary healthcare settings, and refer them for specialized medical management ( Geyti et al, 2018 ). Moreover, improving access to psychiatric care is also recommended, taking the example of developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that 7% of participants of the Check Your Health who completed parts of the health survey did not get an MCS score. 61 These SF-12 non-respondents were more likely to have disadvantaged socioeconomic characteristics, 61 and a fair proportion of this group may suffer from mental distress. 5 Initiation of mental healthcare Additional factors could have influenced initiation of mental healthcare, such as the individual's health literacy Open access and attitudes towards handling of mental health problems.…”
Section: National Registersmentioning
confidence: 99%
“…Screening programs are implemented with the goal of improving the identification of mental health disorders, facilitating referral to treatment, increasing treatment initiation, and improving outcomes. Though evidence on the benefits of population-based screening remains inconclusive, there is some indication that positive mental health screens are associated with treatment initiation, while negative screens are associated with treatment cessation (Geyti et al, 2018; Panaite et al, 2018). Further validation and wider implementation of screening tools for adjustment disorders are important as it may impact treatment initiation and treatment outcomes for individuals with adjustment disorders.…”
Section: Discussionmentioning
confidence: 99%